2020
DOI: 10.1037/str0000158
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sensory processing sensitivity on stress and burnout in nurses.

Abstract: Nursing is a stressful profession, with high levels of burnout among employees. Stress and burnout have been studied extensively in nursing, primarily in terms of organizational and social sources, as well as psychological factors. Studies of Sensory Processing Sensitivity (SPS), the trait that increases one's potential to be overwhelmed by certain aversive stimuli, both internally and environmentally, has recently provided increased empirical insight into the areas of stress and burnout. However, SPS has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
(76 reference statements)
1
17
0
2
Order By: Relevance
“…Thus, the results rejected the null hypothesis 1b. Several studies such as Pindek et al ( 44 ), Czuba et al ( 31 ), and Redfearn et al ( 29 ) found similar findings of the present study. Few studies ( 20 , 21 ) revealed that less powerful employees are more likely to suffer stress than powerful workers and found high occupational stress in junior level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the results rejected the null hypothesis 1b. Several studies such as Pindek et al ( 44 ), Czuba et al ( 31 ), and Redfearn et al ( 29 ) found similar findings of the present study. Few studies ( 20 , 21 ) revealed that less powerful employees are more likely to suffer stress than powerful workers and found high occupational stress in junior level.…”
Section: Discussionsupporting
confidence: 91%
“…Occupational stress is common among garments workers in Bangladesh due to many antecedents of stress ( 26 ). Redfearn et al ( 27 ) revealed that occupational stress has a negative impact on life satisfaction ( 28 ); the study argued that occupational stress is an important factor in determining the life satisfaction and burnout levels ( 29 ). Occupational stress may have a negative effect on companies, such as increased absenteeism and employee turnover, decreased productivity and rising health care costs ( 30 , 31 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nocentini et al, 2018;Pluess & Boniwell, 2015). The interaction between the working environment, SPS, and psychological outcomes has been investigated in a number of working environments, from healthcare (Redfearn et al, 2020), to teaching (Tillmann et al, 2018), and working as an expatriate (Andresen et al, 2018). Throughout the qualitative analysis, it became apparent that there were several multi-faceted environments which resulted in the construction of the subtheme of the same name.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing is consistently ranked as one of the most stressful professions in health care. 1 Stress and burnout have been researched in nursing since the 1970s as a means to retain nurses and impact the nursing shortage. 1 Nurses consistently identify feelings of being overworked, unable to meet the needs of their patients, inadequately prepared, and unprepared to cope with patient deaths as sources of stress which impact their careers.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Stress and burnout have been researched in nursing since the 1970s as a means to retain nurses and impact the nursing shortage. 1 Nurses consistently identify feelings of being overworked, unable to meet the needs of their patients, inadequately prepared, and unprepared to cope with patient deaths as sources of stress which impact their careers. These sources of stress impact nurses in all stages of their careers, nationally and internationally.New graduate nurses (NGNs) are more vulnerable because of various factors, most notably, the practice readiness gap.…”
Section: Introductionmentioning
confidence: 99%